Knowledge hardly translates to reality—A randomized controlled trial on sexual abuse prevention for girls with intellectual disabilities - Reis, Olaf; Häßler, Frank; Daubmann, Anne; Chodan, Wencke (Frontiers in Psychiatry, 2022)
Objective: People with intellectual disabilities (ID) are at higher risk of being sexually abused and developing psychiatric disorders in consequence. The effects of behavior prevention programs for children with ID have rarely been investigated. Previous studies suffer from methodical weaknesses, such as the lack of a control group, small sample size, or invalid outcome measures. This study aimed at demonstrating the efficacy of a prevention program by overcoming these flaws. Method: A group prevention program was developed and evaluated. 106 girls aged from 8 to 12 years with mild ID were enrolled in a randomized controlled study, comparing the training to a sham intervention. Effects were examined in a three-time follow-up design as individual changes in prevention knowledge (board game, verbal reports) and prevention behavior (role-play, in situ tests). Participants’ behaviors were videotaped and rated by three blinded raters. Results: Girls from the intervention group (n = 64) showed improvements in prevention knowledge compared with the control group (n = 39) but did less so for prevention behavior. In situ tests with realistic seduction situations revealed no improvement. The intervention proved to be safe, but several risks need to be considered. Discussion: This is the first study that evaluates a behavioral prevention program on sexual abuse for children with ID on a high level of evidence. Group interventions empowering girls with ID to recognize abuse situations are suitable to enhance sexual prevention knowledge but are less suitable to enhance prevention behavior. Naturalistic settings are inevitable for providing evidence for preventive interventions in children with ID.